Citizens' sustainable, future-oriented energy behaviours in energy transition. (1st February 2020) - Vainio, Annukka; Pulkka, Anna; Paloniemi, Riikka; Varho, Vilja; Tapio, Petri
Abstract: This study explored individuals' engagement in the sustainable energy transition in Finland. Using the attitude-behaviour-context model (Guagnano et al., 1995) and Stern's (2000) typology of environmentally significant behaviours, this study tested the assumption that individuals' engagement in transition is a combination of socio-psychological and contextual (socio-economic) variables and that the active engagement requires individuals to have a future orientation, systemic and self-efficacy, subjective knowledge and a pro-environmental attitude. The survey (N = 1012), representative of the 17−75-year-old Finnish population, was analysed with exploratory factor analysis and linear regression. The socio-psychological variables explained a larger portion of variance than the socio-economic variables in all three types of sustainable energy behaviours. The consideration of future consequences, self-efficacy and knowledge were positively associated with all three types of sustainable energy behaviours. Systemic efficacy was positively associated with and the consideration of immediate consequences was negatively associated with private-sphere environmentalism. The results suggest that individuals' consideration of the immediate and distant future should be included in the socio-psychological models of sustainable behaviours. The results also suggest that policymakers need to focus on strengthening citizens' efficacy beliefs, future orientation and knowledge. Highlights: Non-activist public-sphere behaviours were most frequent. Consideration of future consequences was linked to all types of energy behaviours. Self-efficacy was linked to all types of energy behaviours. Socio-psychological variables explained behaviours more than socio-economic variables.